Efficacy of fecal microbiota therapy in steroid dependent ulcerative colitis: a real world intention-to-treat analysis - Sood, Ajit; Mahajan, Ramit; Juyal, Garima; Midha, Vandana; Grewal, Charanpreet Singh; Mehta, Varun; Singh, Arshdeep; Joshi, Mohan C; Narang, Vikram; Kaur, Kirandeep; Sidhu, Hasrat (Intestinal research, 2019)
Four high-quality randomized controlled trials have proven the efficacy of fecal microbiota transplantation (FMT) in active ulcerative colitis (UC). We assessed the efficacy of FMT in a real-world setting involving steroid-dependent patients with UC. This was a single-center prospective analysis of data from steroid-dependent patients with UC treated with FMT from September 2015 to September 2017 at the Dayanand Medical College, a tertiary care center in India. Fecal samples from random unrelated donors were administered through colonoscopy at weeks 0, 2, 6, 10, 14, 18, and 22. The primary outcome was achievement of steroid-free clinical remission, and the secondary outcomes were clinical response and endoscopic remission at 24 weeks. Modified intention-to-treat analysis was performed, which included subjects who underwent at least 1 FMT. Of 345 patients with UC treated during the study period, 49 (14.2%) had steroid-dependent UC. Of these 49 patients, 41 underwent FMT: 33 completed 7 sessions over 22 weeks according to the protocol, and 8 discontinued treatment (non-response, 5; lost to follow-up, 2; and fear of adverse effects, 1). At week 24, steroid-free clinical remission was achieved in 19 out of 41 (46.3%) patients, whereas clinical response and endoscopic remission were achieved in 31 out of 41 (75.6%) and 26 out of 41 (63.4%) patients, respectively. All patients with clinical response were able to withdraw steroids. There were no serious adverse events necessitating discontinuation. A multisession FMT via the colonoscopic route is a promising therapeutic option for patients with steroid-dependent UC, as it can induce clinical remission and aid in steroid withdrawal.